Maltos istorijos mokslinis paminklas - Kardelis, Naglis (Literatūra, 2010)
Busuttil, Joseph; Fiorini, Stanley; Vella, Horatio Caesar Roger (eds.). Tristia ex Melitogaudo: Lament in Greek Verse of a XII th-century Exile on Gozo. Transcribed, translated and edited by Joseph Busuttil, Stanley Fiorini, and Horatio Caesar Roger Vella. Malta: Farsons Foundation, 2010; pp. CXXX VI, 471; 4 plates. ISBN 978-999320833-4.